Mapalus and Disaster Risk Reduction: Exploring The Spirit of Mapalus Among Tombulu Community - Hilda Vemy Oroh; Gisella Liberty Lasut; Mercy Maggy Franky Rampengan; Joyce Christian Kumaat; Anindya Puspita Putri (Technium Social Sciences Journal, 2023)
The perspective of disaster has shifted from that of an inevitable catastrophe to a natural phenomenon in which the impact can be reduced by strengthening existing capacity within the community. Local capacity played an important part in disaster risk reduction. This is especially true in Indonesia where disaster can strike anytime because of its geographic location. Several studies have been done to identify local wisdom related to disaster risk reduction in Indonesia. However, the study of Mapalus local wisdom in Tombulu people in Tomohon, North Sulawesi related to disaster risk reduction is little to non-existent. Therefore, an effort toward linking Mapalus local wisdom and practices in Tombulu community was made in an attempt to fill the gap in the literature. This paper correlates social and economic capital found in existing Mapalus local wisdom and practices with sustainable livelihood perspective for disaster risk reduction. Future research may refer to this paper as a stepping stone toward unraveling the spirit of Mapalus in disaster risk reduction context.